OPTIMALISASI WAWASAN TENTANG PENTINGNYA PEMAHAMAN TERHADAP LOGO OBAT DAN EDUKASI PENGGUNAAN ANTIBIOTIK BERSAMA LEMBAGA YATIM PIATU ATTAWWABIN - Novan Visia Farmasari; Aura Sabira; Fa’iz Fullala; Hana Fitriyah; Isnaini Izzatin; Kanya Galina; Leni Puspitasari; Leony Adya; Najwa Kayla; Safira Octa; Tyasta Oktavia; Vigi Sela (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Irrational use of antibiotics has become a global issue, with one of the main factors being misused by individuals and professionals. The study focuses on different types of drug logos and the correct use of antibiotics. This community service project aims to increase the knowledge and understanding of adolescents aged 13-17 years regarding drug logos and the correct use of antibiotics. The Community Service was conducted at the Attawwabiin Orphanage Institution on June 7, 2024. The counseling process involved providing educational material to adolescents aged 13-17 years via a smart TV. Education about the differences in drug logos and the correct use of antibiotics began with a pre-test to assess initial knowledge and ended with a post-test to evaluate the understanding of the material presented. The research involved 15 participants, with the pre-test results showing a percentage of 58.2% and the post-test results showing 76.4%. Based on these results, it can be concluded that there was an increase in understanding, indicating that the counseling had a positive impact on educating adolescents aged 13-17 years about various types of drug logos and the correct use of antibiotics.